Maternal Fasting Blood Glucose, Blood Pressure, and Amniotic Fluid Volume with Baby Birth Length and Weight - Hamidah Aula Rusydiana; Mira Dewi; Hadi Riyadi; Lilik Kustiyah (Jurnal Ilmiah Kesehatan (JIKA), 2022)
Maternal health during pregnancy is affecting fetal health in the womb and after birth. This study was conducted to see how maternal fasting blood glucose, blood pressure, and amniotic fluid volume in third semester correlate with baby birth weight and length. The design of this research was observasional in cohort program from third trimester pregnancy until delivery. Result showed that the rising of maternal fasting blood glucose in third trimester was predicted to significantly increasing the baby’s birth weight (b= 7,24, p= 0,025). Inversely, the increase in blood pressure during pregnancy had the potential to lower the weight of the baby (b= -13,94, p= 0,058) although not significanty proven in this study. The correlation between maternal amniotic fluid volume had not shown significant results with neither birth length nor weight of the offspring in this study. It is recommended that pregnant women could maintain their health and also conducted regular health checks of blood glucose, blood pressure, and amniotic fluid volume to avoid pregnancy adverse outcomes if detected.